LEARNING WRITING TEXT REVIEW ON STUDENT STUDENTS USING SAINTIFIC APPROACH - Permana, Asep Kusnadi; Sobari, Teti; Lastari, Deni (IKIP Siliwangi, 2018)
Based on the problem of difficult to write a review text such as determining characteristics, structure, and linguistics to know whether the skills of writing text of junior high school students learn to use a scientific approach is better than using the scientific method? To know the skills of writing an explanatory text for junior high school students using a scientific approach is better than using the scientific method. The research method used in this research is quasi-experiment. The population in this study is a class VIII junior high school students’ with a sample of two classes, amounting to 60 students. Based on the research, the average value of the final test of the experiment is 73 while the control class gets the average score of the final test 70. The results of this study indicate that student learning outcomes by using a scientific approach is better than the lecture method on the subject of writing a review text.